Designing A Combinatorial Java Unit Testing Tool. - Zamli, Kamal Zuhairi; Jamil Klaib, Mohammed Fadel; Azizan, Siti Norbaya (2007)
Software testing relates to the process of executing a program or system with the intent of finding errors. Covering as much as 40 to 50 percent of the development costs and resources, software testing is an integral part of the software development lifecycle.